The Role of Market Segmentation and Competitive Positioning in Increasing Brand Awareness in the Indonesian Retail Industry - Wulandari, Aghnia; Purnomo; Rustandy, Andy (Yayasan Sinergi Kawula Muda, 2024)
This study examines the influence of advertising spending, customer relationship management, market segmentation, and competitive positioning on brand awareness and revenue growth in the retail sector of Indonesia. Data from 300 participants were gathered and analyzed using Structural Equation Modeling-Partial Least Squares version 3, employing a quantitative methodology. The findings demonstrate that all proposed connections are statistically significant and positive, suggesting that making smart investments in advertising, implementing good customer relationship management techniques, conducting precise market segmentation, and establishing a strong competitive position have a substantial impact on increasing brand awareness and driving revenue growth. These findings provide significant information for retail managers and marketers who want to optimize their marketing strategy and achieve sustainable growth in a competitive market.